Microstructure and electrochemical study of equal channel angular pressed Al-Zn alloys - P. Khamnantha (2020)
© Published under licence by IOP Publishing Ltd. This research focuses on the effect of severe plastic deformation (SPD) on microstructure and properties of Al and Al-Zn (in 1, 2, 3, 4, 5 wt%) anodes of Al-air battery. The Al-Zn alloys with a diameter of 12.5 mm and 62.5 mm long were pressed in an ECAP die (press angle $=90°, XP=20°), using route Bc with 2, 4, 6, 8 passes at room temperature. Microstructural characterization was carried out using scanning electron microscope (SEM). The cast samples were solutionized at 450 °C for 1 hr after pressing. Grain size of the as-ECAP samples decreased with an increase of ECAP passes. The smaller grain size resulted in strengthening of Al-Zn. An decrease in grain size was due to significant change in the microstructure from an intensive shear stress after ECAP. Polarization test in a 3.5wt% NaCl solution were used to study electrochemical behaviours of the as-cast and ECAP Al-Zn alloys. The conclusion from the research will be used as a platform to develop Al anodes for Al-air battery in the future.